PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 066050 MEDAN - Pasaribu, Elvin Pasilio; Raja, Bogor Lumban; Abi, Antonius Remigius; Sinaga, Reflina; Simarmata, Ester Julinda (JS (JURNAL SEKOLAH), 2024)
Abstract: This research aims to determine the effect of the Think Pair Share type cooperative learning model on the learning outcomes of class V students in science and science learning at UPT SD Negeri 066050 Medan for the 2023/2024 academic year. The independent variable in this research is the Think Pair Share type cooperative learning model (X) and the dependent variable in this research is student learning outcomes (Y). The method used in this research is quasi-experimental, the sample in this research is 30 students from the class V population. In the Think Pair Share type cooperative learning model, it is obtained from a questionnaire distributed to students and student learning outcomes are obtained from pre-test scores. and Post-test of students in the 2023/2024 academic year. The student learning results show that the pre-test score of class V students is 45.3, while the average post-test score is 88.9. Furthermore, the results of hypothesis testing show t_count is 6.164 while t_table is 2.042. So it is proven that t_table (Ho) is rejected and t_hitung (Ha) is accepted. This shows that there is an influence of the Think Pair Share type cooperative learning model on student learning outcomes.Keywords: Think Pair Share, Student Learning OutcomesAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif tipe Think Pair Share terhadap hasil belajar siswa kelas V pada pembelajaran IPAS UPT SD Negeri 066050 Medan tahun pembelajaran 2023/2024. Variabel bebas dalam penelitian ini adalah model pembelajaran kooperatif tipe Think Pair Share (X) dan variabel terikat dalam pennelitian ini adalah hasil belajar siswa (Y). Metode yang digunakan dalam penelitian ini adalah quasi eksperimen, sampel dalam penelitian ini berjumlah 30 peserta didik dari populasi kelas V. Dalam model pembelajaran kooperatif tipe Think Pair Share didapat dari angket yang disebarkan kepada peserta didik dan hasil belajar peserta didik didapat dari nilai Pre-test dan Post-test peserta didik pada tahun pembelajaran 2023/2024. Hasil belajar peserta didik menunjukkan bahwa nilai peserta didik kelas V Pre-test sebesar 45,3 sedangkan nilai rata-rata Post-test 88,9. Selanjutnya hasil pengujian  hipotesis menunjukkan   sebesar 6,174 sedangkan   sebesar 2,042. Maka terbukti bahwa  (Ho) ditolak dan (Ha) diterima. Hal ini menunjukkan bahwa ada pengaruh model pembelajaran kooperatif tipe Think Pair Share terhadap hasil belajar siswa.Kata kunci: Think Pair Share, Hasil Belajar Siswa